Phosphate fertilization of Mesosetum chaseae in Roraima’s savannas (Research, Society and Development, 2023)
The objective of this work was to evaluate the effect of phosphate fertilization (0, 30, 60 and 120 kg of P2O5 ha-1) on forage production and morphogenetic and structural characteristics of Mesosetum chaseae under natural field conditions in the savannas of Roraima. Phosphate fertilization positively and significantly (P